2004
DOI: 10.1071/mf03198
|View full text |Cite
|
Sign up to set email alerts
|

Does the quantity and timing of fresh water flowing into a dry tropical estuary affect year-class strength of barramundi (Lates calcarifer)?

Abstract: The influence of fresh water flowing into estuaries on biological processes, such as recruitment of juvenile fish, is poorly understood, but important if freshwater resources are to be managed sustainably. Typically, lagged correlations between freshwater flows and fisheries production (i.e. catch) are used to support speculation that flows affect the survival of fish (and thus year-class strength) during their first year of life. The present study compares the relative strength of year classes in an estuarine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 33 publications
8
96
1
Order By: Relevance
“…For example, abundance and survival of early life stages (<1 yr old) of striped bass (Kimmerer et al 2001 are positively related to freshwater flow. For barramundi, strong year classes determined from age structure (Staunton- Smith et al 2004), and also lagged catch data (Robins et al 2005), are positively influenced by freshwater flow. Recruitment variability indicated by age structure for king threadfin in a drytropical estuary was also shown to be positively related to freshwater flow (Halliday et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, abundance and survival of early life stages (<1 yr old) of striped bass (Kimmerer et al 2001 are positively related to freshwater flow. For barramundi, strong year classes determined from age structure (Staunton- Smith et al 2004), and also lagged catch data (Robins et al 2005), are positively influenced by freshwater flow. Recruitment variability indicated by age structure for king threadfin in a drytropical estuary was also shown to be positively related to freshwater flow (Halliday et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using catch curve residuals based on age structure, however, is that a significant time period of recruitment variability can be generated based on only 1 or a few years of sampling. Although the methods of determining recruitment variability relied on assumptions such as relatively constant mortality across age classes (Staunton- Smith et al 2004), the very strong episodic variability in recruitment of bream meant that the patterns were likely to be clear even if the assumptions were not entirely met.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…floodplains and estuaries), whereas in-stream environments are strongly affected by conditions over the rest of the year. Robins et al (2005) and Staunton-Smith et al (2004) have demonstrated the importance of freshwater inflows to tropical estuaries to sustain estuarine fisheries through enhancing habitat access, productivity or recruitment. Recent research on the perennial Daly River has demonstrated the importance of base-flow supported by groundwater inputs for ecosystem production and, consequently, food-web support of higher animals Webster et al 2005).…”
Section: Environmental Flowsmentioning
confidence: 99%